Serum adiponectin relates to shortened overall survival in men with squamous cell esophageal cancer treated with preoperative concurrent chemoradiotherapy: a pilot study - Zemanová, Milada; Staňková, Barbora; Ušiakova, Zuzana; Tvrzická, Eva; Pazdro, Alexandr; Petruželka, Luboš; Zeman, Miroslav (Medical science monitor, 2014)
BACKGROUND: The convergence of nutritional, genetic, and inflammatory factors plays a significant role in the pathophysiology of squamous cell esophageal cancer (SCEC). The parameters of inflammation, indices of nutritional status, and adipocyte-derived hormones such as leptin, adiponectin, and resistin have been shown to be prognostic factors in some gastrointestinal and pancreatic cancers. MATERIAL/METHODS: Forty-two patients with SCEC were subjected to a multimodal regimen of concurrent neoadjuvant chemoradiotherapy (CRT) followed by surgery. We retrospectively analyzed the impact of pretreatment values of serum leptin, adiponectin, resistin, soluble leptin receptor, C-reactive protein, TNF alpha, leukocytes, and indices of nutritional status (BMI, plasma total protein, albumin, cholesterol, and triacylglycerols) on overall survival (OS). RESULTS: Univariate analysis revealed significant a negative correlation between OS and serum adiponectin (p=0.027), and a positive relationship was found between serum albumin (p=0.002), cholesterol (p=0.049) level, and OS. In multivariate analysis, only the trend (p=0.086) for negative serum adiponectin association with the OS was observed. CONCLUSIONS: In men with SCEC treated by neoadjuvant concurrent CRT and esophagectomy, high pretreatment level of serum adiponectin was associated with shorter OS while the serum albumin and cholesterol were associated with longer OS.
Keywords: senioři; proporcionální rizikové modely; analýza přežití; Proportional Hazards Models; spinocelulární karcinom; Survival Analysis; adiponektin; Adiponectin; Esophageal Squamous Cell Carcinoma; Middle Aged; Chemoradiotherapy; chemoradioterapie; Adult; multivariační analýza; Multivariate Analysis; ženské pohlaví; Humans; nádory jícnu; pilotní projekty; Esophageal Neoplasms; lidé středního věku; Pilot Projects; dospělí; Carcinoma, Squamous Cell; Female; Aged; Preoperative Care; předoperační péče; skvamózní karcinom jícnu; lidé